Executive Functions of Swedish Counterterror Intervention Unit Applicants and Police Officer Trainees Evaluated With Design Fluency Test - Vestberg, Torbjörn; Tedeholm, Peter G.; Ingvar, Martin; Larsson, Agneta C.; Petrovic, Predrag (Frontiers in Psychology, 2021)
Executive functions represent higher-order top-down mechanisms regulating information processing. While suboptimal executive functions have been studied in various patient groups their impact on successful behavior is still not well described. Previously, it has been suggested that design fluency - a test including several simultaneous executive functions components mainly related to fluency, cognitive flexibility, and creativity - predicts successful behavior in a quickly changing environment where fast and dynamic adaptions are required, such as ball sports. We hypothesized that similar behaviors are of importance in the selection process of elite police force applicants. To test this hypothesis, we compared elite police force applicants (n=45) with a control group of police officer trainees (n=30). Although both groups were better than the norm, the elite police force applicants had a significantly better performance in design fluency (DF) total correct when adjusting for sex and age (F(1, 71) = 18.98, p < 0.001). To understand how this capacity was altered by stress and tiredness we re-tested the elite police force applicants several days into an extreme field assessment lasting for approximately two weeks. The results suggested that there was a lower than expected improvement in DF total correct and a decline in the DF3-subtest that includes a larger component of cognitive flexibility than the other subtests (DF1 and DF2). Although there was a positive correlation between the baseline session and the re-test in DF3 (r(40) = 0.49, p = 0.001), the applicants having the highest scores in the baseline test also displayed the largest percentage decline in the re-test (r(40) = - 0.46, p = 0.003). In, conclusion, our result suggest that higher order EF that include cognitive flexibility and creativity are of importance in the application for becoming an elite police officer but relatively compromised in a stressful situation. Moreover, as the decline is different between the individuals, the results suggest that applicants should be tested both during baseline conditions and during stressful conditions to fully describe their cognitive capacity.